2016
DOI: 10.1007/s00464-016-4899-5
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic herniation following esophagogastric resectional surgery: an increasing problem with minimally invasive techniques?

Abstract: PODH is a common complication following hybrid esophagectomy and MIO. Given the high mortality from emergency repair, careful thought is needed to identify surgical techniques to prevent PODH forming when minimal access esophagectomy are performed. Upper GI surgeons need to have a low index of suspicion to investigate and treat patients for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 19 publications
4
60
1
Order By: Relevance
“…Thus, the true incidence of HH is most likely between 7% and 10%. These numbers are comparable to a recent meta-analysis and a recent UK study [18,19] that reported an incidence of 5% and 6%, respectively. HH after esophagectomy will become an increasing problem as cancer survival improves.…”
Section: Occurrencesupporting
confidence: 88%
“…Thus, the true incidence of HH is most likely between 7% and 10%. These numbers are comparable to a recent meta-analysis and a recent UK study [18,19] that reported an incidence of 5% and 6%, respectively. HH after esophagectomy will become an increasing problem as cancer survival improves.…”
Section: Occurrencesupporting
confidence: 88%
“…Patients with inoperable disease undergoing ‘open and close’ procedures, with no resection, were excluded. The data set included demographic, treatment and pathology details along with complications. The study was approved by the Queen Elizabeth Hospital clinical audit department.…”
Section: Methodsmentioning
confidence: 99%
“…Hiatal hernia occurs often after esophagectomy with incidence between 5-10% according to recent studies [5,6]. Lower BMI, transhiatal esophagectomy and minimally invasive esophagectomy were associated with higher incidence of postoperative hiatal hernia and the majority of cases (91%) were located in the left chest [5,7].…”
Section: Discussionmentioning
confidence: 99%